Locality and General Vacua in Quantum Field Theory - Colosi, Daniele; Oeckl, Robert (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
We extend the framework of general boundary quantum field theory (GBQFT) to achieve a fully local description of realistic quantum field theories. This requires the quantization of non-Kähler polarizations, which occur generically on timelike hypersurfaces in Lorentzian spacetimes, as has been shown recently. We achieve this in two ways: On the one hand, we replace Hilbert space states by observables localized on hypersurfaces, in the spirit of algebraic quantum field theory. On the other hand, we apply the GNS construction to twisted star-structures to obtain Hilbert spaces, motivated by the notion of reflection positivity of the Euclidean approach to quantum field theory. As one consequence, the well-known representation of a vacuum state in terms of a sea of particle pairs in the Hilbert space of another vacuum admits a vast generalization to non-Kähler vacua, particularly relevant on timelike hypersurfaces.